A new emerging serotype of Vibrio parahaemolyticus in China is rapidly becoming the main epidemic strain. (May 2020) - Chen, X.; Li, Y.; Yao, W.; Wu, T.; Zhu, Q.; Zhang, Y.; Ye, H.; Wang, R.; Zheng, S.; Yu, F.; Chen, W.; Zhu, Z.; et al.
Abstract: Objectives: During surveillance, we found a new type of Vibrio parahaemolyticus named 'O4:KUT-recAin' and studied the phenotypic, pathogenic and epidemiological characteristics of O4:KUT-recAin. Methods: V. parahaemolyticus were isolated from acute diarrhoeal patients in coastal hospitals of China. Serum agglutination test, specific PCR assay, growth curves under different conditions and rabbit diarrhoeal models were using to characterize O4:KUT-recAin. Results: The O4:KUT-recAin strain has a new type of K antigen and a 25 043-bp-large fragment encoding 20 proteins inserted in the housekeeping gene recA . Retrospective analysis found that only one O4:KUT-recAin strain was detected in 563 V. parahaemolyticus strains in 2014; then the proportion increased rapidly and reached 17.8% (105/590) in 2016 and 31.1% (224/721) in 2017, making O4:KUT-recAin the second dominant serotype following O3:K6. O4:KUT-recAin strains (100%, 14/14) exhibited increased acid resistance and could reproduce in medium at pH 4.9, while 92.9% (13/14) of the O3:K6 strains could not grow at this pH value. O4:KUT-recAin could cause diarrhoea and small intestinal tissue lesions in infant rabbits, but its diarrhoeal (93.1%, 27/29) and mortality (78.6%, 22/28) rates were slightly lower than those of O3:K6 (100% 16/16, 100% 16/16). Based on diarrhoea patients, there were no significant differences in the two groups for most clinical symptoms and laboratory results, except media age, haemoglobin and the number of red blood cells in stool samples. Conclusions: O4:KUT-recAin had enhanced acid resistance, was capable of causing infectious diarrhoea in both rabbits and humans, and has become widespread during a short period of time in China.